Libro fotográfico " Las Chichas y su simbología" - Mulky Gallardo, Johanna Mishell (2014)
Chicha is one of the most traditional and emblematic elements of Ecuador among other South American countries. Its importance lies not it be an alcoholic beverage, to the indigenous culture is the link used between Mother Earth and communities. His ancestral meaning has been weakened by the nfluence of Westernism distorting its essence, today the word is used to link to poverty, lack of values or demeaning.